2023
DOI: 10.1186/s12912-022-01139-y
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and care strategies associated with the admission to nursing homes in Germany: a scoping review

Abstract: Background The admission to a nursing home is a critical life-event for affected persons as well as their families. Admission related processes are lacking adequate participation of older people and their families. To improve transitions to nursing homes, context- and country-specific knowledge about the current practice is needed. Hence, our aim was to summarize available evidence on challenges and care strategies associated with the admission to nursing homes in Germany. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Yet this finding was also reflected in two studies and in one systematic review, in which results indicated informal caregivers' worries about whether or not they were making the right decisions for their loved ones, as well as feelings of ambivalence, such as guilt versus relief after a nursing home admission. [33][34][35] According to our findings, experiences in transitional care decision-making and involvement preferences and engagement, in particular, might be explained by the transition's urgency. Older people (and their informal caregivers) who faced an acute transition were often less active or were even totally uninvolved in the decision-making prosses.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Yet this finding was also reflected in two studies and in one systematic review, in which results indicated informal caregivers' worries about whether or not they were making the right decisions for their loved ones, as well as feelings of ambivalence, such as guilt versus relief after a nursing home admission. [33][34][35] According to our findings, experiences in transitional care decision-making and involvement preferences and engagement, in particular, might be explained by the transition's urgency. Older people (and their informal caregivers) who faced an acute transition were often less active or were even totally uninvolved in the decision-making prosses.…”
Section: Discussionmentioning
confidence: 59%
“…The fact that 11 of the 15 informal caregivers in this study were the children of the older person may imply a high level of direct responsibility and commitment and thus burden. Yet this finding was also reflected in two studies and in one systematic review, in which results indicated informal caregivers’ worries about whether or not they were making the right decisions for their loved ones, as well as feelings of ambivalence, such as guilt versus relief after a nursing home admission 33–35 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, Son et al .’s (2019) research concluded that PMHNs do provide various therapies, such as relaxation, aromatherapy and counseling. However, while PMHNs might value psychosocial interventions (Skudlik et al ., 2023), they are often incapable of implementing these practices due to a lack of time or training.…”
Section: Discussionmentioning
confidence: 99%
“…However, this preference for a medical model may not allow PMHNs to fulfill their caring role because it might assign them to being therapeutic assistants for psychiatrists (Skudlik et al ., 2023) or attendants for medical staff (Hayes, 2022).…”
Section: Introductionmentioning
confidence: 99%